2001
DOI: 10.2135/cropsci2001.1862
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid and Protein Changes during Cold Acclimation of Green‐Type Annual Bluegrass (Poa annua L.) Ecotypes

Abstract: nual bluegrass culture on golf course greens in areas experiencing harsh winter conditions. Temperature fluc-Cold acclimation is associated with many metabolic changes that tuations and extreme freezing temperatures at crown lead to increase freezing tolerance. This study was conducted to assess level, occurring during winter and early spring, cause amino acid and protein changes occurring during cold acclimation of green-type annual bluegrass ecotypes cold hardened under both recurrent losses of annual bluegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 31 publications
5
54
0
Order By: Relevance
“…Dörffling et al (1998) reported the existence of a close relationship between coldinduced proline accumulation and cold adaptation in wheat (Triticum aestivum L.). Kaldy and Freyman (1984), Naidu et al (1991) and Dionne et al (2001) also observed an increase of proline in leaves and crowns of wheat and annual bluegrass (Poa annua L.) which was exposed to low temperature. In addition, the constitutively freeze-tolerant single-gene arabidopsis mutant (eskimo1) was higher in both proline and sugar (Xin and Browse 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Dörffling et al (1998) reported the existence of a close relationship between coldinduced proline accumulation and cold adaptation in wheat (Triticum aestivum L.). Kaldy and Freyman (1984), Naidu et al (1991) and Dionne et al (2001) also observed an increase of proline in leaves and crowns of wheat and annual bluegrass (Poa annua L.) which was exposed to low temperature. In addition, the constitutively freeze-tolerant single-gene arabidopsis mutant (eskimo1) was higher in both proline and sugar (Xin and Browse 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Ebdon et al (2002) studied 10 perennial ryegrass cultivars with 10 low temperature ranges to investigated cold tolerance. Among 10 perennial ryegrasses, the high performance cultivars had a mean killing temperature (LT 50 ) of -10.3 o C, and the low performance cultivars had a mean killing temperature of -6.9 o C. Gusta et al (1980) (Dionne et al 2001). However, annual bluegrass has been reported that it is much less tolerate than creeping bentgrass because of ice damage, anoxia condition and crown hydration (Bertrand et al, 2009;Fry and Huang, 2004;Zontek, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the individual amino acids, Asp, Glu, Gln and Pro levels were greatly induced by cold, and these changes were also observed at gene expression level in the case of Pro and Glu. Cold-induced increase in total amino acid content derived mainly from the accumulation of Pro, Glu and Gln in bluegrass (Dionne et al 2001). The increase in Arg content would drive the greater rate of polyamine synthesis which was described in cold-hardened wheat (Kovács et al 2010).…”
Section: Metabolomicsmentioning
confidence: 90%